The Politics of Voice in Duke Ellington’s Beggar’s Holiday (1946) - James O’Leary (Sillages Critiques)
Duke Ellington and John Latouche made a number of pointed references to “highbrow” and “lowbrow” art in their 1947 musical Beggar’s Holiday. I argue that this dichotomy did more than classify; it also politicized the consumption and composition of art. Drawing upon the writings of such critics as Clement Greenberg, Dwight MacDonald, and Archibald MacLeish, my paper revives a 1940s aesthetic discourse that imposed strong divisions between highbrow and lowbrow art. By analyzing a number of recordings of Beggar’s Holiday’s opening song, “In Between,” I demonstrate that Ellington and Latouche simultaneously invoked and undermined this aesthetic dichotomy to make an intervention into post-World War II left-wing political debates.